Oui, il y a des particules de démodulation en français - Steven Schoonjans (CogniTextes, 2014)
Modal particle are generally considered as a characteristic feature of some languages, notably German. For French, some parallels have been noted between the behavior of certain words and that of German particles. However, syntactic differences between German and French are such that some authors are reluctant to classify these French words as modal particles (e.g., Abraham 1991a and Waltereit 2006). In this paper, the relevance of syntactic behavior as a counter-argument to this classification is questioned (bonnement, donc, quand même, seulement, simplement and tout de même).